Correlation among Transforming Growth Factor , Tumour Necrosis Factor- , Prostate Specific Antigen, and Testosterone with Prostate Stromal to Epithelial Ratio in Benign Prostate Hyperplasia - Gede Wirya Kusuma Duarsa (Journal of Global Pharma Technology, 2019)
Introduction: Benign Prostatic Hyperplasia (BPH) occurs due to an imbalance between cell proliferation and the apoptotic process. Many factors influence the growth of the prostate. This study aims to determine which factors among TGF-b, TNF-a,, PSA, testosterone, correlate the most the stromal-to-epithelial ratio of the prostate. Methods: The study was conducted in 83 BPH subjects in several hospitals in Denpasar. From all subjects, blood was taken for PSA and testosterone examination. TGF-b and TNF-a were examined from the histopathological examination of prostate tissue specimens. Data were collected, then statistical analysis was done with SPSS 22.0. Results: From all parameters, only PSA was significantly negatively related to stromal-to-epithelial ratio, although the strength was negatively weak (r -0.28). Multivariate analysis showed that the combination of PSA and TGF- levels had an effect of 10.8% on the epithelial-stromal ratio. Conclusion: PSA showed a significant association with the ratio of prostate epithelial stroma and had an effect value of 10.8% when combined with TGF-bKeywords: Prostate enlargement, Epithelial-stromal ratio, TNF-α, TGF-β, PSA, Testosterone.